ENT 600 : Wan mart food sdn bhd / Muhammad Nizamul Hakim Norzaki ...[et al.] - Hakim Norzaki, Muhammad Nizamul; Awg Osman, Dygku Aniqnatasa; Arzman, Nuriman Aimi; Zainol, Nur Syuhada (2018)
-Student must be able to expose in the business or entrepreneur as they have been taught during class session. Developing an advanced technology could be a basis for development of a Technology-based venture. Thus, this subject taught student to face the challenges and come out with an idea, solution and recommendation to increase the production of company and improvement on their service quality. The course delivery combined both theoretical and practical aspects of technology entrepreneurship. • This report contains the case study that contains the problem and issue. With the intention of completing the case study, an interview has been done at Wan Mart Food Sdn Bhd in Shah Alam, Selzjhgor. The interview session was held by the assistant of the company, Puan Rohanaf/There are several issues that can be improvised such as * maintaining the temperature for food storage, lacked of first-hand expertise, and lack of communication between customers. Thus, all information collected, analysis, and recommendations will take part of this report.